Morphological identification and chemical control of weed population growth in aerobic rice (Oryza sativa L.) system - Aani, Siti Nur Anisah (2018)
Aerobic rice production is a revolutionary way of rice cultivation in well-drained, non- puddled, and non-saturated soils condition with very minimal water requirements. However, weed is one of the most troublesome issues in aerobic rice field due to no standing water to suppress weed germination upon early stage of rice development. To overcome this constraint and plan for future weed management, fundamental studies of weed population growth under aerobic rice is important. Two aerobic rice varieties, AERON 1 and MRIA 1 cultivated in three different types of soils collected from three different fields around Malaysia were evaluated to identify most dominance weed invasion in the glasshouse trial. Survey of weed population in the actual field of aerobic rice was also carried out in order to check the similarities and difference of weed infestation in control and uncontrolled environment. The most dominant weed species found in glasshouse study and field survey regardless of soil textures and aerobic rice varieties were Leptochloa chinensis and Cyperus iria. Controlling weeds during the critical period of crop growth is one of the early steps in designing integrated weed management (IWM) and crucial for better yield and quality. Hence, determinations of the critical period for weed control (CPWC) study were conducted in main and off season by using a four parameter log-logistic model. Based on 5% Accepted Yield Loss (AYL), aerobic rice field should be weed free during 8 DAS to 45 DAS in the off season while, 14 DAS to 41 DAS in the main season. The acceptable of 10% AYL in the off season ranged from 12 DAS until 40 DAS in the off season while, 23 DAS until 37 DAS in the main season. Experiment of weed-crop competition by using additive design was also carried out. Identification of two most predominant weed species from experiment 1, Leptochloa chinensis and Cyperus iria were used. Different level of weed infestation against constant aerobic rice density was assessed. Infestation of Cyperus iria in aerobic rice MRIA 1 at 7 different levels of weed density recorded higher impact on rice growth and production compared to Leptochloa chinensis intervention based on the findings recorded. A total of 13 herbicides treatments consist of sequential application in single and combination herbicide were tested to evaluate the response of weed flora towards different approaches. A single application of herbicides such as Penoxsulam and Imazapyr- isopropylammonium did not provided maximum control compared to the sequential application of Bispyribac-sodium fb Bentazon/MCPA and Pretilachlor fb Propanil/Thiobencarb. Study of weed population in aerobic rice, critical period of weed control, weed-crop competition and suitable herbicides application could help farmers in facing difficulties with weed management along the cultivation seasons. Besides that, these approaches will enable weed scientists to make an important contribution towards the development of weed control options with minimal herbicides doses. Thus, awareness on the importance of improved cultural practices, their impact on weed suppression, and benefits to the ecosystem would be helpful in the implementation of crop interference strategies.